Incidence and outcomes of ventilator associated pneumonia in pediatric patients: an observational study - Ashok Kumar, Ashok Kumar; Singh, Suresh N.; Singh, Vijay K.; Singh, Priyanka; Sharma, Bhoopendra; Tiwari, Harish C. (International Journal of Contemporary Pediatrics, 2024)
Background: Ventilator associated pneumonia (VAP) is very common in pediatric intensive care unit (PICU) intubated patients and also responsible for major morbidity and mortality. Usually, it develops after 48 hours of mechanically ventilated patients, its incidence increases as the duration of time increases and it is a major risk factor for VAP. The present study was carried out to know the overall incidence of VAP in mechanically ventilated patients in PICU. Methods: The study was carried out in PICU of the department of pediatrics, B. R. D. Medical College, Gorakhpur from October 2020 to October 2021. Patients aged between 1 year to 15 years were included in the study. Results: There were 50 (59.5%) patients’ male and 34 (40.5%) patients’ female under investigation. The clinical pulmonary infection score (CPIS) values ranged from the mean value of 4.38±2.30 at 36th hours to 7.33±1.92 at 96th hours of intubation. VAP was present in 23 (27.3%) patients while 62 (73.8%) patients were having no VAP. Among VAP associated patients, 14.3% were Acinetobacter positive, 5.95% were Klebsiella positive and 3.57% were E. coli positive. Conclusions: Parameters of CPIS associated with VAP revealed that Acinetobactor was comparative more common organism and the age group of 1 to 5 years was more sensitive. VAP can be reduced by decreasing the duration of mechanical ventilation.